(untitled) (Research, Society and Development, 2023)
Objective: To evaluate the effectiveness of Integrative and Complementary Practices in the chronic pain process. Methodology: This is an integrative review with a qualitative and descriptive approach. Data collection was carried out in the following databases: Virtual Health Library (VHL), National Library of Medicine (PubMed) and SienceDirect, and took place in September 2022. The inclusion criteria were: scientific articles with full text free, in Portuguese, English and Spanish and published between 2018 and 2022, which agree with the theme explored and the guiding question. Results and Discussions: The initial screening resulted in 1187 articles in the VHL, Pubmed, ScienceDirect databases. After filtering, reading the title and abstracts, reading the articles in full and excluding those that were not in accordance with the research objectives or were duplicates, 11 publications were selected as they were relevant to this review. The PICS that were analyzed and introduced in the study were Osteopathy, Chiropractic, Massage, Tai Chi, Yoga, Hypnosis and Music Therapy and Acupuncture. Through the studies analyzed, it was evidenced that the PICS discussed can be effective in the chronic pain process. Final Considerations: The effectiveness of PICS in relation to chronic pain is well known, however, it is necessary to expand studies on the topic to improve discussions on which methods provide greater effectiveness depending on the type of chronic pain of each patient who underwent treatment. these integrative and complementary practices, since the topic presents a low number of studies.